2022
DOI: 10.3390/molecules27082502
|View full text |Cite
|
Sign up to set email alerts
|

(20R)-Panaxadiol as a Natural Active Component with Anti-Obesity Effects on ob/ob Mice via Modulating the Gut Microbiota

Abstract: Obesity is an important cause of diseases such as type 2 diabetes, non-alcoholic fatty liver and atherosclerosis. The use of ingredients extracted from traditional Chinese medicine for weight loss is now receiving more and more attention. Ginseng has been recorded since ancient times for the treatment of diabetes. The (20R)-Panaxadiol (PD) belongs to the ginseng diol type compounds, which are moderately bioavailable and may remain in the intestinal tract for a longer period of time. This study investigated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Lachnospiraceae , one of the 16S taxa that was associated with lower stool proline, expresses proline reductase PrdA and has been reported to compete with other microbiota for proline and other amino acids ( Mefferd et al, 2020 ). Muribaculaceae , which was also linked to lower stool proline in our model, is associated with anti-obesity effects and produces butyrate, a short chain fatty acid that attenuates lung inflammation in murine models of allergic airway disease ( Cait et al, 2017 ; Xu et al, 2020 ; Ye et al, 2021 ; Lv et al, 2022 ). However, we did not observe changes in short chain fatty acids measured from cecal tissue in this model ( Supplement Figure 6 ).…”
Section: Discussionmentioning
confidence: 86%
“…Lachnospiraceae , one of the 16S taxa that was associated with lower stool proline, expresses proline reductase PrdA and has been reported to compete with other microbiota for proline and other amino acids ( Mefferd et al, 2020 ). Muribaculaceae , which was also linked to lower stool proline in our model, is associated with anti-obesity effects and produces butyrate, a short chain fatty acid that attenuates lung inflammation in murine models of allergic airway disease ( Cait et al, 2017 ; Xu et al, 2020 ; Ye et al, 2021 ; Lv et al, 2022 ). However, we did not observe changes in short chain fatty acids measured from cecal tissue in this model ( Supplement Figure 6 ).…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, the conversion of ginseng into PPT under the influence of gut microbiota enhances the activity of beneficial bacteria, including Bacteroides , Eubacterium , Bifidobacterium , and Fusobacterium . Additionally, certain monomers of ginseng, such as panaxadiol and Rk3, have been found to significantly lower the Firmicutes / Bacteroidetes (F/B) ratio in obese mice, , highlighting their potential as therapeutic targets for obesity-related diseases. Notably, G-Rg1 has exhibited significant effects on the gut microbiota of colitis patients, specifically regulating the abundance of Lachnospiraceae , Staphylococcus , Bacteroide , and Ruminococcaceae_UCG_014 .…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus is an essential probiotic that can prevent obesity by altering the gut microbiota in obese mice (Zhang et al, 2022). It has been reported that Lactobacillus can cut down sugars for energy and produce large amounts of lactic acid, which can increase satiety after a meal (Lv et al, 2022). Moreover, Lactobacillus converts glycosides into aglycones to improve their bioavailability and bioactivity by producing extracellular b-glucosidase.…”
Section: Discussionmentioning
confidence: 99%